Essays on David Hume, medical men and the Scottish Enlightenment : industry, knowledge and humanity - Emerson, Roger L. (Science, technology, and culture, 1700-1945., 2008)
The Scottish Enlightenment was a period of intellectual and scientific progress in a country previously considered to be marginal to the European intellectual scene. This volume of essays considers a broad range of themes pertinent to the period, from the European Enlightenment and the Scots relation to it, to Scottish social history and its relation to religion, science and medicine.